2022
DOI: 10.1038/s41598-022-17017-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased temporal stride variability contributes to impaired gait coordination after stroke

Abstract: Heightened motor variability is a prominent impairment after stroke. During walking, stroke survivors show increased spatial and temporal variability; however, the functional implications of increased gait variability are not well understood. Here, we determine the effect of gait variability on the coordination between lower limbs during overground walking in stroke survivors. Ambulatory stroke survivors and controls walked at a preferred pace. We measured stride length and stride time variability, and accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…Recently, Patel et al [29] reported that both temporal and spatial gait variability correlated with inter-limb coordination of walking in PwS, signifying that not only intra-limb coordination is required for safe and stable walking. The observed relations in both reports should be further examined to test whether these relations are causal, because if this is the case, rehabilitation programs for PwS would benefit from adding intra- and inter-limb coordination training.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Patel et al [29] reported that both temporal and spatial gait variability correlated with inter-limb coordination of walking in PwS, signifying that not only intra-limb coordination is required for safe and stable walking. The observed relations in both reports should be further examined to test whether these relations are causal, because if this is the case, rehabilitation programs for PwS would benefit from adding intra- and inter-limb coordination training.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not examine which of these factors improved. Furthermore, increased spatial and temporal gait variability in patients with stroke has been reported ( 15 ). Evaluation from this perspective, in addition to the percentage of gait acquisition, may lead to more accurate decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This result in CA patients may be related to a deficit in lower limb coordination reflecting arrhythmic muscle contractions between flexors and extensors during gait. Otherwise, gait variability in post-stroke individuals was found to be augmented in stride time, which contributes to the incoordination since it directly involves the accuracy and the consistency of gait coordination [57]. In a similar way, TBI patients tend to show an increased step time variability, which is strongly correlated with dynamic instability, which further increases when the gait task becomes more challenging [58].…”
Section: Clinical Considerations About Gait and Postural Dysfunctionsmentioning
confidence: 97%